2015
DOI: 10.1108/mbe-04-2015-0019
|View full text |Cite
|
Sign up to set email alerts
|

Does environmental performance affect companies’ environmental disclosure?

Abstract: Purpose - This study aims to verify the presence, evolution and determinants of voluntary environmental disclosure from companies listed on the Milan Stock Exchange. The authors examined documentation of listed firms from 2006 and 2009. These years immediately precede and follow Italian legislative decree n. 32/2007, which introduced (albeit on a voluntary basis) disclosure of environment-related company information. Design/methodology/approach - The authors’ approach utilizes multivariate regression analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
41
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 86 publications
3
41
0
6
Order By: Relevance
“…Secondly, the position of corporate managers in the disclosure of social responsibility information cannot be ignored. Fontana et al [8] examined the documentation of listed firms and pointed out that in many cases, the lack of disclosure information is caused by the lack of relevant awareness of business managers. Grigoris Giannarakis [9] used the least-squares dummy variable model (LSDV) to examine the influence of plausible variables on the ESG disclosure score and its sub-categories and then pointed out that we should pay attention to the disclosure of information and, according to the industry, have a corresponding focus, which provides a basis for us to establish an ESG evaluation system for Chinese power companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Secondly, the position of corporate managers in the disclosure of social responsibility information cannot be ignored. Fontana et al [8] examined the documentation of listed firms and pointed out that in many cases, the lack of disclosure information is caused by the lack of relevant awareness of business managers. Grigoris Giannarakis [9] used the least-squares dummy variable model (LSDV) to examine the influence of plausible variables on the ESG disclosure score and its sub-categories and then pointed out that we should pay attention to the disclosure of information and, according to the industry, have a corresponding focus, which provides a basis for us to establish an ESG evaluation system for Chinese power companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This reduces emissions while at the same time improving the enterprise's social reputation and increasing consumer satisfaction [37,38]. Studies have shown that when pollution of the atmosphere rises, the government will tend to strengthen environmental regulation and enterprises will pay more attention to the atmospheric environment for this reason [39]. Furthermore, pollution of the atmosphere will lead consumers to call upon enterprises to strengthen their environmental protection behaviors and strengthen their CSR [40].…”
Section: The Regulatory Role Of the Atmospheric Environment On The Rementioning
confidence: 99%
“…As a result, some scholars proposed that the ratio of tradable shares positively affects CSR [48,49]. Stefano et al (2015) [50] found that the level of voluntary environmental disclosure tends to increase with the growth of public partners in the ownership structure. However, based on an empirical analysis in the Chinese electrical industry, Liu (2013) [51] simultaneously verified a negative relationship between CSR and the ratio of tradable shares as well as a positive relationship between CSR and profitability.…”
Section: The Interactions Of Csr and Ownership Structure On Economic mentioning
confidence: 99%